Crafting Success: A Strategic Exploration of Technical and Conceptual (Hard) Skills of Modern Social Media Managers - Alateya, Abbas Alwan Ghazi; Baskaran, Shathees (Business Management and Strategy, 2024)
The role of a social media manager in companies has evolved into a critical function for brand visibility and engagement. This article explores the technical and conceptual skills essential for success in this role. It begins by highlighting the increasing importance of social media in business strategies, identifies the challenges social media managers face, and then delves into the research gap regarding the nuanced skills required. The literature review examines the existing body of knowledge on both technical and conceptual skills, providing insights into their significance. The discussion section synthesizes this information, offering a holistic understanding of the skills necessary for effective social media management. The article concludes with recommendations for future studies to enhance the knowledge of this dynamic field.